Future Socionomic Specialists’ Dispositional Self-development - Oksana Los; Оlena Razumova; Nataliia Hoi (Insight: the psychological dimensions of society, 2023)
The purpose was to conduct empirical research and theoretically substantiate the correlation between the parameters of dispositional self-development of future specialists of the socioeconomic profile and the factors of professional growth. It is substantiated and generalized that dispositional self-development is the readiness and inclination of future specialists of the socionomic profile to self-education, self-creation, and self-improvement, which is capable of ensuring permanent professional growth and professional development. Participants of the empirical study are seekers of three academic degrees (Bachelor’s, Master’s, and Doctor of Philosophy) studying at three Ukrainian higher education institutions, and are future socioeconomic specialists. The age of the research participants ranged from 17 to 32 years (M=21.06; Me=21.00; SD=5.84), with a total of n=132. Methods: “Dispositional Characteristics of Personality Self-Development” (DCPSD) (Kuzikova, 2017); “Personal Orientation Inventory” (РОІ) (Shostrom, 1964); “The Method of Diagnosing the Individual’s Motivation to Achieve Success and Avoid Failure” (MDIMASAF) (Elers, 2002); methods of mathematical statistics. Results. In the comparison of low, medium, and high levels of dispositional self-development parameters, no statistically significant differences were found (р>.05). It was discovered that the dispositional self-development parameters “Need for Self-Development”, “Conditions of Self-Development”, and “Mechanisms of Self-Development” had statistically significant correlations with the parameters of self-actualization and motivation to achieve success (р<.050; р<.010). When compared to other parameters, it is proved that the “Need of Self-Development” (NSD) was a reflection of the phenomenon’s cognitive intentions and was the most important parameter of the respondents’ dispositional self-development (nine significant correlations – the greatest number). Discussion and сonclusions. It was substantiated and proven that dispositional self-development is an important component of future specialists’ self-actualization, self-education, and quality professional training. The scientific findings should be applied in educational and professional activities.